Consumo de alcohol y su incidencia en la conducta de los estudiantes de 1ro, 2do, 3ro, de bachillerato de la sección nocturna del Colegio Nacional Técnico Pasaje, del cantón Pasaje periodo lectivo 2012-2013. - Yunga Yunga, Nery Eraldo (2013)
The investigation began with the reference to the object of study literature review, this information was selected and saved through the signing for the construction of the chapters of the theoretical framework, the problematization allowed develop the problem-objectives and hypothesis system, once operationalized the variables involved in each scenario, a process of gathering information that allowed them show began.